Skin Improvement with Antioxidant Effect of Yuja (Citrus junos) Peel Fractions: Wrinkles, Moisturizing, and Whitening - Young Yun Jung; In Jin Ha; Mina Lee; Kwang Seok Ahn (Antioxidants, 2022)
Yuja (Citrus junos) has been cultivated and used for food and medicinal purposes in China and Korea. Its antioxidant, anti-wrinkle, moisturizing, and whitening effects were evaluated in HaCaT, HDF, and B16F10 cells. UVB has been known to cause cellular stress and the production of reactive oxygen species (ROS). Ambivalence of oxidative stress has been reported; however, excessive levels of ROS contribute to skin aging through the loss of elasticity and collagen fibers of connective tissue in the dermis. Skin aging is one of the biological processes that is affected by various factors, including UVB. Pro-Collagen I and hyaluronic acid contents were measured in UVB-irradiated HaCaT and HDF cells to evaluate the anti-wrinkle and moisturizing effects of Yuja-peel (YJP) fractions in -EA (ethyl acetate), -Hex (hexane), and -BuOH (butanol). The expression of matrix metalloproteinases (MMPs) involved in collagen degradation was confirmed to be inhibited by YJP fractions at both the protein and mRNA levels. Filaggrin and serine palmitoyltransferase (SPT), which are moisturizing factors, were induced by YJP fractions. B16F10 cells were treated with α-MSH to induce hyperpigmentation, and then the whitening efficacy of YJP fractions was verified by observing a decrease in melanin content. Overall, our results contribute to the development of various novel skin-improving cosmetics and pharmaceuticals with YJP fractions as active ingredients.